Protocolo de preparo da criança pré-escolar para punção venosa, com utilização do brinquedo terapêutico - Martins, Maria do Rosário (2001)
This exploratory - descriptive study aims at elaborating a protocol, using therapeutic play, for the preparation of preschool children to venous puncture and also at testing its efficiency and applicability. The children that attended the play session were more cooperative when they were punctured. They understood the need and technical aspects of this clinical procedure; manifested their feelings, elaborated familiar and hospital situations that resulted in a better relationship with the other children and the nursing team. Authors concluded that this protocol is feasible and useful and suggested that it should be incorporated in the nursing care plan to hospitalized children.